{Double – photon exclusive processes with heavy quark – heavy antiquark pairs in high-energy Pb-Pb collisions at LHC} - Klusek-Gawenda, M.; Szczurek, A; Machado, MVT; Serbo, VG (Phys. Rev. C, 2011)
n/a
n/a